Elements of optimal paediatric palliative care for children and young people: An integrative review using a systematic approach. Issue 4 (December 2015) - Virdun, Claudia; Brown, Nicola; Phillips, Jane; Luckett, Tim; Agar, Meera; Green, Anna; Davidson, Patricia M.
Summary: Background: Models of palliative care need to address the unmet needs of children, young people and families. Objective: To undertake an integrative review to identify the key elements of optimal paediatric palliative care from the perspectives of children and young people with palliative care needs and their parents. Data sources: Electronic databases including CINAHL, Medline, PsycINFO and AMED searched using combined terms for palliative care, service models and children along with reference lists of included studies. Study selection: Peer reviewed empirical studies reporting on evaluation of paediatric palliative care by children and young people with palliative care needs (0–19 years), or their families, published in English, between 2000 and 2013. The views of health professionals and grey literature were excluded. Quality appraisal completed by two researchers, consensus reached following discussion. Data extraction and synthesis: Data extracted by two researchers, entered into an electronic proforma and synthesised using a narrative approach. Results: Seven studies were identified of which two were quantitative, one was qualitative and four were mixed methods. Synthesis highlighted the need for tailored support enabling flexibility in care, with specific reference to location of care and access to psychosocial support, 24 h specialist support, respite care and sibling support. Conclusions: Paediatric palliative care should be flexible, responsive and tailored to the needs of children and their families. Robust evaluation of models of care that incorporate these elements is required to inform optimal care.